2018
DOI: 10.3389/fneur.2018.00536
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous PLA2G6 Mutation Leads to Iron Accumulation Within Basal Ganglia and Parkinson's Disease

Abstract: Mutations of PLA2G6 gene are responsible for PARK14, an autosomal recessive L-DOPA responsive dystonia/parkinsonism with early/adult onset. This phenotype possesses an high clinical variability, which consists in the occurrence of cerebral and cerebellar atrophy, iron accumulation in the basal ganglia, and cognitive decline. This report describes a PD patient carrying an heterozygous PLA2G6 mutation, which was identified also in his PD affected sister. This patient is characterized by a L-DOPA responsive typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In our study, we identified four rare damaging heterozygous mutations in AR genes ( Table 5 ), which suggested a potential role in the PD pathogenesis (Makovac et al, 2016; Ferese et al, 2018). Other studies suggested that approximately 5%–10% of sporadic EOPD patients carried heterozygous mutation in AR-PD-associated genes (Periquet et al, 2003; Clark et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our study, we identified four rare damaging heterozygous mutations in AR genes ( Table 5 ), which suggested a potential role in the PD pathogenesis (Makovac et al, 2016; Ferese et al, 2018). Other studies suggested that approximately 5%–10% of sporadic EOPD patients carried heterozygous mutation in AR-PD-associated genes (Periquet et al, 2003; Clark et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, the previously described mutations can cause malfunction in the metabolism of dopamine in the striatum and brain network changes, leading to cognitive impairment (Hilker et al, 2001; Khan et al, 2002; Benbunan et al, 2004; Ricciardi et al, 2014; Makovac et al, 2016). Moreover, other authors suggested that heterozygous mutations in PLA2G6 may also contribute to the susceptibility for developing PD (Ferese et al, 2018), as some PLA2G6 heterozygous mutations were presented in PD patients (Bower et al, 2011; Lu et al, 2012). We assume that the I898M damaging mutation in the CP gene, which plays an important role in the iron and copper metabolism in the brain (Zhao et al, 2018), could intensify the risk of developing PD.…”
Section: Discussionmentioning
confidence: 99%
“…A single case report suggested that heterozygous PLA2G6 mutation might lead to Parkinson disease 14 (PARK14). 14 Of interest, Lewy body pathology is also present in PLA2G6 associated neurodegeneration (PLAN) .…”
Section: Discussionmentioning
confidence: 99%
“…The PLA2G6 gene encodes calcium-independent phospholipase A2 beta enzyme (iPLA 2 β), which participates in cell membrane homeostasis, mitochondrial function, fatty acid oxidation, and calcium signaling (3, 4). PLA2G6 dysfunction has been proved as a pathogenic factor for PLA2G6-associated neurodegeneration (PLAN) (5), including infantile neuroaxonal dystrophy (INAD), neurodegeneration with brain iron accumulation (NBIA), and PLA2G6-related autosomal recessive dystonia-parkinsonism in its disease spectrum (6).…”
Section: Introductionmentioning
confidence: 99%
“…PLA2G6 dysfunction has been proved as a pathogenic factor for PLA2G6-associated neurodegeneration (PLAN) (5), including infantile neuroaxonal dystrophy (INAD), neurodegeneration with brain iron accumulation (NBIA), and PLA2G6-related autosomal recessive dystonia-parkinsonism in its disease spectrum (6). Several mutations in PLA2G6 gene were reported to be associated with both atypical autosomal recessive parkinsonism (3, 7, 8), and sporadic early-onset PD (9, 10). PLA2G6 mutant parkinsonism cases showed alpha-synuclein pathology (11) in the substantia nigra and locus ceruleus, and one third of patients might be accompanied by iron accumulation (12).…”
Section: Introductionmentioning
confidence: 99%